The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21103618
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and Lipid Mediators Associated with the Risk and Pathology of Ischemic Stroke

Abstract: Stroke is a severe neurological disorder in humans that results from an interruption of the blood supply to the brain. Worldwide, stoke affects over 100 million people each year and is the second largest contributor to disability. Dyslipidemia is a modifiable risk factor for stroke that is associated with an increased risk of the disease. Traditional and non-traditional lipid measures are proposed as biomarkers for the better detection of subclinical disease. In the central nervous system, lipids and lipid med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 167 publications
(181 reference statements)
2
34
0
Order By: Relevance
“…Between the two subtypes of ischemic ABI models, PM and TM, these ischemic injuries harbored few differences in their transcriptomic signatures. However, we found that lipidomics of PM and TM revealed variations between them during the first 72H after injury, showing that lipid metabolism is sensitive to ischemia, which is consistent with the previous investigation 48 .…”
supporting
confidence: 92%
“…Between the two subtypes of ischemic ABI models, PM and TM, these ischemic injuries harbored few differences in their transcriptomic signatures. However, we found that lipidomics of PM and TM revealed variations between them during the first 72H after injury, showing that lipid metabolism is sensitive to ischemia, which is consistent with the previous investigation 48 .…”
supporting
confidence: 92%
“…As already mentioned above, lipids not only serve as structural components, but also exert crucial biological roles as signaling molecules. This aspect is extensively discussed in the review article proposed by Kloska and collaborators, who focused their attention on the role of lipid mediators in the risk and pathology of ischemic stroke [18]. Notably, a lively metabolism of polyunsaturated fatty acid has been documented in ischemic brain, and different lipid mediators are implicated in the neuroprotective or neurodegenerative effects occurring in the post-stroke brain tissue.…”
mentioning
confidence: 99%
“…Mechanisms underlying neuroprotection and lung protection reported include interfering with vascular resistance, vasopermeability change, anti-oxidation, and anti-inflammation. 55,56 However, we consider that improvement of hemodynamics plays the major role in reservation of neurological and pulmonary function due to their consistency of trends.…”
Section: Discussionmentioning
confidence: 99%